2009
DOI: 10.1086/598965
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind, Placebo‐Controlled Trial of Maraviroc in Treatment‐Experienced Patients Infected with Non‐R5 HIV‐1

Abstract: Clinicaltrials.gov identifier NCT00098748 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
122
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 12 publications
2
122
1
4
Order By: Relevance
“…This finding supports the fact that an antiretroviral effect is necessary to observe the specific immune effects of MVC in relation to these markers. Thus, MVC will not have any immunomodulatory effect on patients who are insensitive to the drug, at least on the parameters studied herein, a finding which is in contrast to what has been previously suggested (23). Surprisingly, the MVC-specific effect after 8 days was an increase in CD8 ϩ T-cell activation and senescence levels.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This finding supports the fact that an antiretroviral effect is necessary to observe the specific immune effects of MVC in relation to these markers. Thus, MVC will not have any immunomodulatory effect on patients who are insensitive to the drug, at least on the parameters studied herein, a finding which is in contrast to what has been previously suggested (23). Surprisingly, the MVC-specific effect after 8 days was an increase in CD8 ϩ T-cell activation and senescence levels.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, it is important to explore whether new drugs can have an impact on HIV progression-related biomarkers. Maraviroc (MVC) (7), the first CCR5 (R5) antagonist approved for the treatment of HIV-1 infection, has been proposed as a drug with an immunomodulatory effect independent of its antiviral activity (1,23,25). Moreover, it has been recently suggested that MVC-containing cART can facilitate a greater reduction in immune activation and inflammation markers than conventional cART (10).…”
mentioning
confidence: 99%
“…Moreover, our results are also consistent with the data from the A4001029-study, a Phase 2b clinical trial, where patients carrying non-R5 viruses were treated with maraviroc-containing regimen. This study has indeed shown the suppression of viremia below 50 copies/ml in 27% of patients with D/M-tropic viruses at week 48 of a maraviroc-containing regimen (Saag et al, 2009). In particular, a marked decrease of viremia (close to that achieved in patients carrying R5 virus) at week-12 was observed in patients with a rate of X4-tropic viruses <10% (Swenson et al, 2009).…”
Section: Discussionmentioning
confidence: 80%
“…This was done in order to determine the sensitivity and reproducibility of conventional sequencing results as this nonhomogeneous clinical sample is representative of samples which are the most difficult to detect by conventional sequencing approaches. Samples from the phase 3 clinical trials of maraviroc, the MOTIVATE and A4001029 studies (7,25), which had both population-based sequence data and matched deep-sequencing data (26) in both the forward and reverse direction, were used as a wider data set for comparison (n ϭ 1,521 samples). Two independent samples of peripheral blood mononuclear cells (PBMC) from 39 patients from the MOTIVATE study and from 62 patients from the A401029 study were also sequenced.…”
Section: Methodsmentioning
confidence: 99%